Trichothecenes in food and feed: Occurrence, impact on human health and their detection and management strategies. (March 2022) - Mahato, Dipendra Kumar; Pandhi, Shikha; Kamle, Madhu; Gupta, Akansha; Sharma, Bharti; Panda, Brajesh Kumar; Srivastava, Shubhangi; Kumar, Manoj; Selvakumar, Raman; Pandey, Arun Kumar; Suthar, Priyanka; Arora, Shalini; et al.
Abstract: Trichothecenes (TCNs) are the mycotoxins produced by many fungal species such as Fusarium, Myrothecium, and Stachybotrys and pose a considerable health risk. Based on their characteristic functional moieties, they are divided into four categories: Type A (T-2, HT-2, diacetoxyscirpenol (DAS), harzianum A, neosolaniol (NEO) and trichodermin), Type B (deoxynivalenol (DON), nivalenol (NIV), trichothecin and fusarenon X), Type C (crotocin) and Type D (satratoxin G & H, roridin A and verrucarin A) with types A and B being the most substantial. TCNs cause growth retardation in eukaryotes, suppress seedling growth or regeneration in plants and could be a reason for animal reproductive failure. Due to the increased frequency of occurrence and widespread distribution of TCNs in food and feed, knowledge of their sources of occurrence is essential to strategise their control and management. Hence, this review provides an overview of various types and sources of TCNs, the associated biosynthetic pathways and genes responsible for production in food and feed. Further, various processing and environmental effects on TCNs production, detection techniques and management strategies are also briefly outlined. Graphical abstract: Image 1 Highlights: Trichothecenes are mycotoxins produced primarily by Fusarium species. The primary source of trichothecenes in human and animal diet is cereals. Trichothecenes toxicity can lead to various health problems. Trichothecenes in food and feed can be minimized using various processing and degradation techniques.